Enhancement of Shelf Life of Grated Beetroots - López Osornio, María de las Mercedes (1997)
Microbiological quality in grated beetroots was studied. The vegetable was washed with cold water (8°C) or with chlorinated water (8°C and 252 mg active chlorine per liter water) and packaged in trays wrapped in high permeability film (PVC). Storage temperatures were 0, 4, and 20°C. Aerobic count colonies (ACC), fungi and yeasts, and lactose fermentative bacteria were determined. Representative colonies were identified. The results obtained showed that the treatment with chlorinated water caused significant decreases (P < 0.05) in the initial yeast counts and total aerobic counts. Treatment with cold chlorinated water significantly decreased the yeast counts and PCA counts after 3 days at 0 and 4°C. The change to 20°C caused significantly increased (P < 0.05) PCA counts in the grated beetroots (107 to 108 CFU/g). The microorganisms predominant among the isolates from fresh grated beetroots were gram negative bacteria (80%) and yeasts. None of the trays with grated beetroots contained molds. Some of the bacteria identified were Micrococcus lute us, Acinetobacter spp., Corynebacterium spp., and Enterobacteriaceae.